Effectiveness On The Implementation Of Minister Of Health Decree Number 6424 Of 2021 On Covid-19 Vaccination Doses 3 And 4 - Fitri, Syari Ramdhania; Nurlaily, Nurlaily; Seroja, Triana Dewi (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: COVID-19 vaccination is an important initiative in the Indonesian government's strategy to manage the pandemic and achieve herd immunity. Based on the Decree of the Minister of Health Number 6424 of 2021, the government intends to increase the coverage of the third and fourth doses as part of the national vaccination program.Purposes of the Research: The purpose of this study seeks to evaluate the effectiveness of this policy in Riau Islands Province, especially to examine the obstacles faced in achieving adequate vaccination coverage.Methods of the Research: Using an empirical legal methodology with a sociological legal approach, this study analyzes data related to the implementation of vaccination and the factors that cause the absorption of the third and fourth doses to be suboptimal.Results Main Findings of the Research: Key findings show that although the administration of the first and second doses yielded positive results, the uptake of the third and fourth doses was still hampered by a variety of challenges, including legal factors, law enforcement factors, as well as a lack of public awareness and cultural challenges. Based on these findings, the government is advised to increase public outreach efforts, increase socialization and legal education, improve regulations and policies, strengthen law enforcement, provide incentives, education based on local wisdom, and cultural incentive programs. In addition, policies that prioritize public understanding and engagement are critical to achieving desired vaccination goals.